Clinical Management of Dystocia Due to Lateral Deviation of Fetal Head in Sheep - Karthik; Neha samaikya; Sandeep; sampath; Satish Martha; M.Rajashri; E.Sunil Anand Kumar (The Indian Veterinary Journal, 2023)
A nondescript ewe was presented to VCC, Warangal with full term and straining. As per the Animal’s history, fetal fluid was lost 6 hours before and was straining since then. Pervaginal examination revealed right lateral deviation of head and neck (fetal malposture) which was successfully manipulated by mutational operations and delivered a dead fetus. Ewe was treated with antibiotic and supportive therapy which was recovered uneventfully.